Coronavirus disease 2019 (COVID-19) vaccine breakthrough infections among healthcare personnel, December 2020-April 2021 - Katelin B. Nickel; Victoria J. Fraser; Hilary M. Babcock; Jennie H. Kwon; for the CDC Prevention Epicenters Program (Cambridge University Press, 2022)
Coronavirus disease 2019 (COVID-19) vaccine effectiveness in the early months of vaccine availability was high among healthcare personnel (HCP) at 88.3% for 2-doses. Among those testing positive for severe acute respiratory coronavirus virus 2 (SARS-CoV-2), those with breakthrough infection after vaccination were more likely to have had a non-work-related SARS-CoV-2 exposure compared to unvaccinated HCP.